FREQUENCY OF DEPRESSION AND SOMATIC SYMPTOMS IN PATIENTS ON INTERFERON ALPHA/RIBAVIRIN FOR CHRONIC HEPATITIS C - Shakoor, Abdul; Shafqat, Farzana; Mehmud, Tafazzul e Haque; Akram, Mohammad; Riaz, Sarah; Iqbal, Zafar; Khan, Anwaar A (Journal of Ayub Medical College Abbottabad, 2010)
Background: Large numbers of patients suffering from Chronic Hepatitis C (HCV) are seeking treatment with interferon alpha (IFN) because of significant advances in overall improvement in the course of HCV and its complications. Objectives were to estimate the frequency of depression and somatic symptoms in patients on interferon alpha/ribavirin treatment for chronic hepatitis C. Methods: It was an observational study conducted in the out-patient Department of Gastroenterology Shaikh Zayed Hospital, Lahore during a period of three months, i.e., from September to November 2008. One hundred consecutive patients undergoing interferon alpha/ ribavirin treatment for chronic HCV were included in the study. All patients, irrespective of age, sex or duration of treatment were administered with a check list of common physical complaints and DSM-IV symptoms for Major Depressive Episode. Results: Out of a total of 100 subjects 37 were male and 63 were female. In all, 39 (39%) patients fulfilled the diagnostic criteria of DSMIV for Major Depressive Episode. Major Depression was more common in female 28 (44.4%) as compared to male 11 (28.7%) patients. Somatic symptoms were common in all the patients but they were reported more frequently by patients with Major Depression compared to those without Major Depression. Myalgias, headache, joint pain, nausea/vomiting, abdominal pain and palpitation were the most common physical symptoms. Conclusion: Major Depression and somatic complaints are a common consequence of interferon alpha/ribavirin treatment for chronic hepatitis C. All patients receiving this treatment should be periodically assessed for the detection of these side effects to promptly address relevant treatment options. Keywords: Interferon Alpha, Ribavirin, Hepatitis C, Depression